Patterns of Socialization in the Lithuanian Biographies: Dimensions of Gender and Time - Kraniauskienė, Sigita (Sociologija. Mintis ir veiksmas, 2002)
The article explores models of socialisation and gender identity at different stages of life-course and in different historical periods. Considerations are based on biographical approach and use data of the biographical contest “Story of My Life”. During the process of socialisation gender identity is institutionally transmitted to individuals as a pattem of social behaviour. Gender identity embodies its own ideology and strategies of interpersonal interactions, where personal biography is a narrative about these interactions shaped by gender. Socialisation evolves as a constant interaction between author and his/her social milieu shaping identity of a person. Each member of society is involved in the process, but their age and in some respect the historical circumstances differently sets their status of a subject or an object of socialisation. Time (in this case a time period when individual was born and was more intensively engaged in socialisation) is a feature of modern bio graphy (a concept of V. Kavolis) and it allows to identify different worldviews of narrating individuals. Time demarcates traditional and modern worldviews and deterrnines reflexivity of the author. Nevertheless, analysing the collected biographies it is hard to differentiate pure traditional or pure modern ones. To be more precise, the features of modern biographies are usually incorporated into traditional-epic narratives of life stories. On the one hand the relationship of traditional/modem can be understood as a constituent of the narrative, on the other hand it is a representation of the modern worldview in reflexive narration. The traditional framework of narrative contains definite models of gender identities. Traditional duality differentiation of gender roles and structure of patriarchal opposition - is presented as social reality in biographical narratives. The differentiation is imperative and is a warrant of social order and gender identity. But several narratives about the self neglect such manifest differentiation of gender roles. Main distinction of feminine or masculine biographies is based on different perception of self-estimation and social integration.